Toxicity interaction of cooper and salinity on Perez frog life stages - Santos, Bárbara Rosa da Fonseca (2011)
Populations of amphibians are declining worldwide. Among the major causes for such decline are chemical contamination and climate changes (e.g. increase in temperature, salinization of coastal freshwater ecosystems). Actually, the group of amphibians may be very sensitive to these stressors as they possess a thin and permeable skin with no physical protection that allows cutaneous respiration but also the diffusion of chemical agents present in the environment. Furthermore, their biphasic life cycle exposes amphibains both to aquatic, terrestrial and atmospheric contamination, potentiating the period of exposure. Consequently, it is necessary to understand the effects that chemical contamination may pose to this group of organisms and how other factors may influence their sensitivity to chemical stress. Accordingly, the present work intended at evaluating how life stage and the combination with other stressors may influence the toxicity of copper to the Perez´s frog Pelophylax perezi (Seoane). To attain this main goal, two specific objectives were delineated: (i) to compare the sensitivity of different life stages, embryos versus tadpoles, to copper (Experimental design 1), and (ii) to evaluate the influence of increased salinity (an indirect effect of climate changes in coastal freshwater lagoons) on the toxicity of copper to embryos and tadpoles of P. perezi (Experimental design 2). For this, eggs at Gosner stage 10-11 and tadpoles at Gosner stage 25 were used to carry out 96h exposure assays. For the first experiment, the two life stages were exposed to a gradient of copper plus a control (FETAX). In the second experiment, embryos and tadpoles were exposed to combinations of copper and NaCl (to simulate an increased salinity) in a complete bifactorial experimental design. In the two experiments the following endpoints were monitored: (i) for embryos, mortality was registered every 24h and at the end of the assay the final body length and malformations rate of surviving larvae were assessed; (ii) for tadpoles mortality and swimming behavior were monitored every 24h. Additionally, at the end of the experimental desing 2 the enzymatic activity, of surviving larvae/tadpoles, was quantified for catalase (CAT), cholinesterase (ChE), glutathione S-transferase (GST) and lactate dehydrogenase (LDH). The obtained results showed that embryos were less sensitive to copper than tadpoles (aproximately 50% of mortality at 1.6 mg/L Cu and LC50=0.93 mg/L Cu, respectively). Furthermore, it was observed that NaCl did not influence the lethal toxicity of copper to tadpoles, but, it significantly reduced the copper toxicity to embryos. Regarding enzymatic responses, a clear and consistent response was not observed for the tested treatments. However, for some copper concentration, the presence of NaCl induced an increase of the activity of CAT, relatively to that observed when orgaisms were exposed solely to copper, both for embryos and tadpoles. Also, in some copper concentrations, the presence of NaCl caused an increase or decrease in the activity of LDH in embryos and tadpoles, respectively. In addition, and contrarirly to what was reported for copper, it was observed that embryos were more sensitive to increased salinity (NaCl) than tadpoles. The results obtained in the present study, highlighted the need, within the context of ecological risk evaluation, to characterize the sensitivity of different life stages of amphibians to different chemicals and to the combination of diverse stressors.